Physico-chemical quality of surface water within Long Banga upper Heart of Borneo Island catchments - James Gerusu, Geoffery; Ismail, Nur Bazilah (International Journal of Advanced Research, 2017)
Assessment of physico-chemical water quality of Long Banga upper catchment in Heart of Borneo area, Sarawak, Malaysia was conducted during Scientific Expedition 2016. The purpose was to ascertain the water quality level within these highland catchments. The results were compared with Malaysia Interim National Water Quality Standards (INWQS) standard for water quality. Results showed positive levels to aquatic life in general, with high dissolved oxygen concentrations with an average of 7.1 mg/l and also less conductivity, TDS and TSS in all sampling points. Water samples results from Sg. Ano revealed slight variation of high concentration of COD which fall under Class III of water quality standards compared to other streams. High concentration of COD might be attributed to production of organic acids during breakdown of organic matter. Generally, the results obtained indicated that physio-chemical properties of all 27 sampling points within Long Banga catchment was characterized as unpolluted and conserved in its natural state.